VD_FINDINFO ML / 2014 / 145 vom 1. Mai 2014 - VD Tribunal cantonal (2014)
MAINLEVÉE DÉFINITIVE, SUSPENSION DE LA PROCÉDURE, DOMMAGE IRRÉPARABLE, CESSION LÉGALE, AVOCAT, DÉPENS | 57 LP, 58 LP, 59 LP, 60 LP, 61 LP, 62 LP, 81 al. 1 LP, 85 LP, 85a LP, 88 LP, 46 LPAv, 126 CPC (CH), 319 let. b ch. 1 CPC (CH), 8 TDC